Acute Posterior Multifocal Placoid Pigment Epitheliopathy Sharing Characteristic OCT Findings of Vogt-Koyanagi-Harada Disease - Yuta Kitamura; Toshiyuki Oshitari; Masayasu Kitahashi; Takayuki Baba; Shuichi Yamamoto (Case Reports in Ophthalmological Medicine)
A 17-year-old male presented with acute bilateral paracentral scotomata and blurred vision. Funduscopic examination showed bilateral macular serous retinal detachment and yellow-white placoid lesions at the level of retinal pigment epithelium. OCT study showed typical VKH disease findings with marked choroidal thickening and macular serous retinal detachment partly with subretinal septa in both eyes. FA demonstrated hypofluorescence at the placoid lesions in the early phase and hyperfluorescence in the late phase. Laboratory investigation showed negative result for HLA-DR4 serotype and the patient’s cerebrospinal fluid test values were within normal range. We made the diagnosis of APMPPE from these results. At 2-month follow-up without the use of corticosteroids, OCT reexamination showed complete amelioration of subretinal fluid in both eyes. Patchy pigmentary lesions also resolved clinically with partial chorioretinal scars. The results in this case suggested OCT findings in APMPPE patients could be similar to characteristic features usually found in acute VKH disease. We recommend comprehensive assessments such as FA, cerebral spinal fluid analysis, and HLA typing which help in leading proper diagnosis.